2016
DOI: 10.1007/s12639-016-0830-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ovicidal activity of Peganum harmala seeds extract on the eggs of Fasciola hepatica

Abstract: seeds extract has been previously reported to have antimicrobial and other medicinal properties. The aim of this study was to evaluate the ovicidal activity of the methanolic extract of seeds against the eggs of The phenolic compounds of the methanolic extract of seeds were identified by HPLC analysis. Catechin, rutin, p-Coumaric acid, chloregenic acid and hesperetin were found to be the major phenolic compounds. eggs were collected from the gall bladder of naturally infected sheep. The eggs were exposed to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(40 reference statements)
2
12
0
1
Order By: Relevance
“…Biological activity of P. harmala may be due to such components. Antioxidant, antidiabetic, antiviral, and antimicrobial activities of P. harmala are determined in different recent studies (11). Nematollahi and Ghazi (30) reported that P. harmala extract had no significant scolicidal activity that was in accordance with the current study finding.…”
Section: Normal Salinesupporting
confidence: 90%
See 2 more Smart Citations
“…Biological activity of P. harmala may be due to such components. Antioxidant, antidiabetic, antiviral, and antimicrobial activities of P. harmala are determined in different recent studies (11). Nematollahi and Ghazi (30) reported that P. harmala extract had no significant scolicidal activity that was in accordance with the current study finding.…”
Section: Normal Salinesupporting
confidence: 90%
“…However, increasing the exposure time led to higher mortality rate, but the increase was not remarkable (compared with the control group). Recent studies revealed that P. harmala contains bioactive natural components such as catechin, rutin, and p-coumaric acid (11). Biological activity of P. harmala may be due to such components.…”
Section: Normal Salinementioning
confidence: 99%
See 1 more Smart Citation
“…Тому дослідники, проводячи вивчення хімічних та біологічних методів дезінвазії за різних гельмінтозів сільськогосподарських і свійських тварин, використовували її в експериментах (Brewster et al, 2003;Pecson and Nelson, 2005;Voloshyna, 2010;Mun et al, 2012;Katakam et al, 2014). Проте останнім часом окремі автори пропонують використовувати як тест-культури яйця конкретних збудників гельмінтозів, проти яких і ведеться боротьба, оскільки такі дані є більш об'єктивними (Braga et al, 2008;Naidoo et al, 2016;Moazeni, 2017). Проведеними дослідженнями встановлено, що засіб "Віросан" володіє вираженими дезінвазійними властивостями відносно яєць нематод, що підтверджується дослідами інших вчених (Klymenko et al, 2018).…”
Section: таблицяunclassified
“…In order to eliminate and prevent environmental contamination by invasive elements, there is a well-developed health improvement system that combines animal deworming and disinfestation of environmental objects (Naidoo et al, 2016;Moazeni et al, 2017). Experience shows that the main and the most effective among the avail-Citation: Melnychuk, V., & Yuskiv, I.…”
Section: Introductionmentioning
confidence: 99%